The Study of Preference on Skill-Based Training Among Household Women in Gudalur Town - Anishma Manoharan; Aparna S; Fathima Jennath (International Journal of Community Health Nursing And Practices, 2025)
This study explores the need for skill-based training among women in households in Gudalur town, identifying preferred training types, choice-influencing factors, and participation barriers. Skill development is a critical component of women's empowerment, promoting financial autonomy and social mobility. Surveys were conducted with 50 women, who were chosen using a stratified random sampling method. The survey comprised demographics, most preferred training courses, perceived benefits, and participation barriers. Descriptive statistics was used to establish the most desired skills, and thematic analysis looked into motivational and social issues. The results showed that computer literacy, embroidery, handicrafts, and tailoring were the most desired skills, mostly for self-employment and additional income. Time restrictions, domestic responsibilities, and resource constraints were however major barriers. The study underscores the requirement for accessible, affordable, and flexible training interventions to promote improved participation and facilitation of socio-economic development for women. Fostering improvement through policy and institutional support towards meeting these issues can empower household women with practical skills and enhance their economic livelihood. Policymakers and institutions providing training ought to institute strategic interventions towards enabling more inclusive skill development and strengthening economic independence, and social empowerment of women within Gudalur town.
Keywords: Data collection; Gudalur town; Skill-based training; financial independence; household women; income generation; policy initiatives; qualitative analysis; self-employment; stratified random sampling; women’s empowerment